Human Chronology in the Periods of Variations of Environmental Processes (Global Journal of Science Frontier Research, 2018)
The chronological system based on the periods of variations of water runoff of the Neva and Dnieper Rivers with the length of 28 and 29 years is composed. It starts from the Creation of the World by the Hebrew Calendar and divides the human past for two eras: consisting from the 7 ages the Era of Separated World and the Era of United Humanity, which boundary is the 1924. The world history is presented as the successive complication of human communities which new forms originated during the completion of the ages as the results of grandiose events which could be interpreted as the Great Revolutions opening for humans the new directions of the social development.
Keywords: cycles of environmental processes; forms of communities of people; great revolutions; directions of the social development of humanity